Pengaruh Kedisiplinan dan Kompetensi Terhadap Peningkatan Kinerja Guru Pada Madrasah Ibtidaiyah (MI) DDI Kabupaten Mamasa - Ibrahim; Andi Hendra Syam; Andi Irfan (Jurnal Online Manajemen ELPEI, 2023)
This study aims 1) to find out and prove the effect of discipline on teacher performance at Madrasah Ibtidaiyah (MI) DDI Kab. Mamasa, 2) to find out and prove the influence of competence on teacher performance at Madrasah Ibtidaiyah (MI) DDI Kab. Mamasa, 3) to find out and prove the effect of discipline and competence on teacher performance at Madrasah Ibtidaiyah (MI) DDI Kab. Mamasa. Data collection is done through documentation, observation, and questionnaires. The teacher sample is 70 respondents. Data processing consists of descriptive analysis, correlation analysis and regression analysis The results showed that with a significant level of 5% and degrees of freedom df1 = 2 and df2 = 67 then f table obtained (2:69) = 3.150. Based on the ANOVA test or F test from the SPSS output, it can be seen that the f count is 28,874 > 3.150 the f table value and the probability is 0.000 <0.05. More precisely, the calculated F value is compared to the F table where if F count > F table then simultaneously discipline and competence have a positive and significant effect on teacher performance at Madrasah Ibtidaiyah (MI) DDI Mamasa Regency. This means that the hypothesis of the two researchers is accepted.